Decision Support System for Selection of Online Shopping Applications for MSME Product Marketing Using AHP and TOPSIS Methods - Enok Tuti Alawiah; Dwi Andini Putri (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
MSMEs are business actors who support economic growth and create new jobs for the community. Currently, many business actors use online shopping applications to market their products. One of the reasons is because now many buyers are switching to online shopping. There are many types of online shopping applications. However, research needs to be done to choose the right online shopping application to market their products so that they are right on target and can increase sales turnover. The AHP Topsis method is used to assist the decision making process. AHP is used to calculate comparison values and create a hierarchical structure, while topsis helps in the decision-making process based on the criteria and alternatives offered. The results showed that the final preference value was 0.51 for attractive promotions and the number of active users of the application. Then the alternative applications that can be used are the Shopee and Tokopedia shopping applications based on the five alternatives offered.